Effect of iron ore tailings industrial by-product as eco-friendly aggregate on mechanical properties, pore structure, and sulfate attack and dry-wet cycles resistance of concrete. (December 2022) - Liu, Kangning; Wang, Sheliang; Quan, Xiaoyi; Jing, Wu; Xu, Jin; Zhao, Nan; Liu, Bo
Abstract: The large stockpiles of iron ore tailings (IOTs) have put an overload on the environment. Effective utilization of IOTs is beneficial to environmental protection and sustainable development. Therefore, this study aims to provide a comprehensive and in-depth evaluation of using IOTs as eco-friendly aggregates instead of river sand (RS) to produce IOTs concrete (IOTC) and revealed the change mechanism of macroscopic properties from the mesoscopic and microscopic point of view. Different IOTs replacement ratios, namely 0 %, 20 %, 40 %, 60 %, 80 %, and 100 % were used to prepare IOTC. The mechanical properties, sulfate attack and dry-wet (D-W) in the water, 3 % and 5 % Na2 SO4 solution resistance were investigated. Moreover, the pore structure was investigated based on nuclear magnetic resonance (NMR) non-destructive testing techniques. Finally, the crystal composition and micro-morphology of IOTC were characterized using X-ray diffraction (XRD) and scanning electron microscope (SEM). Results indicated that the IOTC with 40 % IOTs had the lowest porosity and denser microstructure, considerably improving the compactness of the IOTC, which exhibited the best mechanical properties and sulfate attack and D-W cycles resistance. It was worth noting that during D-W cycling in the water, 3 %, and 5 % Na2 SO4 solution, the D-W damage of IOTC is relatively small at the initial stage of D-W cycles and then increases rapidly with the D-W cycles increasing. The D-W damage of IOTC in the 5 % Na2 SO4 solution is significantly higher than that in the 3 % Na2 SO4 solution and water. After 200 D-W cycles, the large pores in IOTC are easier to form in 5 % Na2 SO4 solution, and the number of corrosion products is further formed. The gradual increase in the number of larger pores is the main factor affecting the D-W resistance. The obtained research results will further promote the sustainable application of IOTs as eco-friendly materials in concrete.